Tingkat Kesukaan terhadap Minuman Cocktail Harvey Wallbanger Berbahan Dasar Jus Jeruk Siam Kintamani Segar dan Jus Jeruk Dalam Kemasan - Ni Kadek Eni Juniari (Pusat Penelitian & Pengabdian kepada Masyarakat Politeknik Pariwisata Bali, 2020)
The purpose of this study was to compare the level of preference for a Harvey Wallbanger cocktail made from fresh Kintamani Siamese orange juice with packaged orange juice. A descriptive qualitative data analysis through organoleptic tests in the form of hedonic tests on the indicators of Acidity, Sweetness, Aroma, Color, Balance, Presentation was applied. While the panelists in this study were 20 people consisting of bartenders, academics and moderately trained panelists who like cocktails. The results showed that the Harvey Wallbanger cocktail using fresh Kintamani Siamese orange juice got a value of 3.30 with the interpretation value being very favorable, while the Harvey Wallbanger cocktail using packaged orange juice got a value of 2.49 with the interpretation value. normal. This shows that the Harvey Wallbanger cocktail made from fresh Kintamani Siamese orange juice is preferred over the Harvey Wallbanger cocktail which uses packaged orange juice.